Does Disaster Education of Teenagers Translate into Better Survival Knowledge, Knowledge of Skills, and Adaptive Behavioral Change? A Systematic Literature Review. Issue 6 (20th October 2014) - Codreanu, Tudor A.; Celenza, Antonio; Jacobs, Ian
Abstract An increasing number of people are affected worldwide by the effects of disasters, and the United Nations International Strategy for Disaster Reduction (UNISDR) has recognized the need for a radical paradigm shift in the preparedness and combat of the effects of disasters through the implementation of specific actions. At the governmental level, these actions translate into disaster and risk reduction education and activities at school. Fifteen years after the UNISDR declaration, there is a need to know if the current methods of disaster education of the teenage population enhance their knowledge, knowledge of skills in disasters, and whether there is a behavioral change which would improve their chances for survival post disaster. This multidisciplinary systematic literature review showed that the published evidence regarding enhancing the disaster-related knowledge of teenagers and the related problem solving skills and behavior is piecemeal in design, approach, and execution in spite of consensus on the detrimental effects on injury rates and survival. There is some evidence that isolated school-based intervention enhances the theoretical disaster knowledge which may also extend to practical skills; however, disaster behavioral change is not forthcoming. It seems that the best results are obtained by combining theoretical and practical activities in school, family, community, and self-education programs. There is a still a pressing need for a concerted educational drive to achieve disaster preparedness behavioral change. School leavers' lack of knowledge, knowledge of skills, and adaptive behavioral change are detrimental to their chances of survival. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>TA</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Codreanu</surname> </string-name>, <string-name><given-names>A</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Celenza</surname></string-name>, <string-name><given-names>I</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Jacobs</surname></string-name>. Does disaster education of teenagers translate into better survival knowledge, knowledge of skills, and adaptive behavioral change? A systematic literature review . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>6</issue>):<fpage>1</fpage>-<lpage>14</lpage></mixed-citation>.